A numerical analysis of the characteristics of interfacial waves on the onset of flooding in an inclined pipe. (November 2020) - Zhao, Jingjing; tao, Hanzhong; Cheng, Jianjie; Li, Wei; Fu, Lijun
Highlights: Focused on the effect of contact angle and liquid velocity on the behavior of liqud film and the development of flooding waves using the VOF method. An analytical force model is proposed to study the effect of contact angle on the onset of flooding including the shear force. The histograms of the forces at various contact angles and liquid velocities are investigated for the mechanism of the onset of flooding. The results of the numerical simulation provide ideas for the data divergence of different flooding correlations. Abstract: The purpose of the present study is to investigate the characteristics of interfacial waves on flooding phenomena in an inclined pipe. The effects of liquid velocity and contact angle on the waves at the onset of flooding are studied with a two-dimensional computational fluid dynamic model. Flooding in a 30° inclined pipe is observed by using the Volume of Fluid (VOF) method. It is found when the contact angle is equal to 120°, the pipe wall cannot form a uniform liquid film and the gas velocity required on the onset of flooding decreases as the contact angle and liquid velocity increase. For a detailed understanding of the effects of contact angle and liquid velocity, an analytical forces model is proposed on the flooding waves, including gravity Fgw, the pressure of the gas core Fpc, pressure variations in the liquid film Fpl, wall shear force Fws, interfacial shear force Fss and surface tension force Fσ . Through the quantitative calculation of all forces, it is found that the amplitude and length of the flooding wave increase with liquid velocity. As the contact angle increases, the crests become sharper. Further, through analyzing the histogram distribution of the forces, the increase of the contact angle will change the mechanism of flooding from carrying droplets to rising waves. It provides a theoretical basis for the development of mechanistic models to predict the onset of flooding in the future.